Continuous versus routine EEG in patients after cardiac arrest: Analysis of a randomized controlled trial (CERTA). (July 2022) - Urbano, Valentina; Alvarez, Vincent; Schindler, Kaspar; Rüegg, Stephan; Ben-Hamouda, Nawfel; Novy, Jan; Rossetti, Andrea O.
Graphical abstract: Abstract: Background: Electroencephalography (EEG) is essential to assess prognosis in patients after cardiac arrest (CA). Use of continuous EEG (cEEG) is increasing in critically-ill patients, but it is more resource-consuming than routine EEG (rEEG). Observational studies did not show a major impact of cEEG versus rEEG on outcome, but randomized studies are lacking. Methods: We analyzed data of the CERTA trial (NCT03129438), including comatose adults after CA undergoing cEEG (30–48 hours) or two rEEG (20–30 minutes each). We explored correlations between recording EEG type and mortality (primary outcome), or Cerebral Performance Categories (CPC, secondary outcome), assessed blindly at 6 months, using uni- and multivariable analyses (adjusting for other prognostic variables showing some imbalance across groups). Results: We analyzed 112 adults (52 underwent rEEG, 60 cEEG, ); 31 (27.7%) were women; 68 (60.7%) patients died. In univariate analysis, mortality (rEEG 59%, cEEG 65%, p = 0.318) and good outcome (CPC 1–2; rEEG 33%, cEEG 27%, p = 0.247) were comparable across EEG groups. This did not change after multiple logistic regressions, adjusting for shockable rhythm, time to return of spontaneous circulation, serum neuron-specific enolase, EEG background reactivity, regarding mortality (cEEG vs rEEG: OR 1.60, 95% CI 0.43–5.83, p = 0.477), and good outcome (OR 0.51, 95% CI 0.14–1.90, p = 0.318). Conclusion: This analysis suggests that cEEG or repeated rEEG are related to comparable outcomes of comatose patients after CA. Pending a prospective, large randomized trial, this finding does not support the routine use of cEEG for prognostication in this setting. Trial registration: Continuous EEG Randomized Trial in Adults (CERTA); NCT03129438; July 25, 2019.